Role of solar wind speed and interplanetary magnetic field during two-step Forbush decreases caused by Interplanetary Coronal Mass Ejections - Bhaskar, Ankush; Vichare, Geeta; Arunbabu, K.P.; Raghav, Anil (My University, 2016)
The relationship of Forbush decreases (FDs) observed in Moscow neutron monitor with the interplanetary magnetic field (B) and solar wind speed (Vsw) is investigated in detail for the FDs associated with Interplanetary Coronal Mass Ejections (ICMEs) during 2001–2004. The classical two-step FD events are selected, and characteristics of the first step (mainly associated with shock), as well as of complete decrease (main phase) and recovery phase, are studied here. It is observed that the onset of FD occurs generally after zero to a few hours of shock arrival, indicating in the post-shock region that mainly sheath and ICME act as important drivers of FD. A good correlation is observed between the amplitude of B and associated FD magnitude observed in the neutron count rate of the main phase. The duration of the main phase observed in the neutron count rate also shows good correlation with B. This might indicate that stronger interplanetary disturbances have a large dimension of magnetic field structure which causes longer fall time of FD main phase when they transit across the Earth. It is observed that Vsw and neutron count rate time profiles show considerable similarity with each other during complete FD, especially during the recovery phase of FD. Linear relationship is observed between time duration/e-folding time of FD recovery phase and Vsw. These observations indicate that the FDs are influenced by the inhibited diffusion of cosmic rays due to the enhanced convection associated with B A. Bhaskar ankushbhaskar@gmail.com 1 Indian Institute of Geomagnetism, Kalamboli Highway, New Panvel, Navi Mumbai 410 218, India 2 The GRAPES-3 Experiment, Cosmic Ray Laboratory, Raj Bhavan, Ooty 643 001, India 3 Department of Physics, University of Mumbai, Mumbai 400 098, India the interplanetary disturbances. We infer that the inhibited cross-field diffusion of the cosmic rays due to enhanced B is mainly responsible for the main phase of FD whereas the expansion of ICME contributes in the early recovery phase and the gradual variation of Vsw beyond ICME boundaries contributes to the long duration of FD recovery through reduced convection–diffusion.
Keywords: Solar wind; Interplanetary electric field; Forbush decreases; Interplanetary Coronal Mass Ejections